Artificial glycopolypeptide conjugates: simple synthesis of lactose- and N, N′-diacetylchitobiose-substituted poly( l-glutamic acid)s through N- β-glycoside linkages and their interaction with lectins - Kobayashi, Kazukiyo; Tawada, Emiko; Akaike, Toshihiro; Usui, Taichi (Biochimica et biophysica acta, 1997)
Poly(glutamic acid)s carrying lactose- and N, N′-diacetylchitobiose residues were synthesized via a simple two-step procedure. The oligosaccharides were treated with ammonium hydrogen carbonate and the resulting N- β-glycosylamine was coupled with pendant carboxyl groups of poly( l-glutamic acid) in the presence of a mixture of benzotriazol-1-yl-oxy-tris(dimethylamino)phosphonium hexafluorophosphate (BOP) and 1-hydroxybenzotriazole (HOBt) in dimethyl sulfoxide. The oligosaccharide incorporated as pendant N-glycosides was estimated by 1H-NMR spectroscopy to be 30 mol% (or 45 wt%) for lactose and 27 mol% (46 wt%) for chitobiose. The glycopolypeptide carrying N, N′-diacetyl-chitobiose inhibited hemagglutination activity of wheat germ agglutinin (WGA) much more strongly (about 10 6 times) than N, N′-diacetylchitobiose itself. The high activity is due to the cluster or high density effect of the glycopolypeptides.